Phenylobacterium soli sp. nov., isolated from arsenic and cadmium contaminated farmland soil - Li, Xuexue; Yu, Ying; Choi, Lina; Song, Yali; Wu, Minghan; Wang, Gejiao; Li, Mingshun (International journal of systematic and evolutionary microbiology, 2019)
A Gram-stain-negative, facultative anaerobic, non-motile and rod-shaped bacterial strain, designated LX32 , was isolated from arsenic and cadmium contaminated farmland soil. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain LX32 was closely related to Phenylobacterium hankyongense HKS-05 (97.7 % sequence similarity), Phenylobacterium kunshanense CCTCC AB 2013085 (97.4 %) and Phenylobacterium deserti CCTCC AB 2016297 (97.1 %). The average nucleotide identity values of the whole genome sequences of LX32 /P. hankyongense HKS-05 , LX32 /P. kunshanense CCTCC AB 2013085 and LX32 /P. deserti CCTCC AB 2016297 were 79.8, 77.9 and 77.5 %, respectively. Its genome size was 4.02 Mb, comprising 3998 predicted genes with a DNA G+C content of 70.1 mol%. The major fatty acids were C15 : 0, C16 : 0 and summed feature 8 (comprising C18 : 1ω7c and/or C18 : 1ω6c). The polar lipid profiles consisted of phosphatidylglycerol, aminophospholipid, seven glycolipids and two unidentified polar lipids. The predominantly respiratory quinone was ubiquinone-10. Based on polyphasic analyses, the isolate is considered to represent a novel species of the genus Phenylobacterium, for which the name Phenylobacterium soli sp. nov. is proposed. The type strain is LX32 (=KCTC 62522=CCTCC AB 2018055).